Biomedicina Slovenica in COBISS - Dornik, Ema (Organizacija znanja, 2007)
The paper describes the creation of the bibliographical collection called Biomedicina Slovenica (BS) and its connection to the COBISS system. BS is a specialised bibliographical collection for the area of biomedcine in the process of development by the Institute of Biomedical Informatics of the Faculty of Medicine in Ljubljana since 1976. At the end of 2007, the BS contained nearly 130,000 bibliographic records, of which 91,955 were also integrated into COBISS. An automatic transfer of records from the BS collection to COBISS has been available for ten years and 97 percent of the records created by IBMI have been added to the COBISS system this way. In the recent period, we have developed tools for automatic downloading of records from the COBISS.SI system and PubMed, yet this currently constitutes only 0.5 percent of all the records entered in the BS. We have contributed 3.4 percent of records to the COBISS system.
Keywords: Biomedicina Slovenica; COBISS; COBISS.net; gradnja podatkovnih zbirk; prevzemanje bibliografskih zapisov